2019
DOI: 10.1523/eneuro.0417-18.2019
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic Strengths Dominate Phasing of Motor Circuit: Intrinsic Conductances of Neuron Types Need Not Vary across Animals

Abstract: Visual Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Variability of intrinsic currents in STG neurons may be compensated by cell-type-specific co-regulation of different voltage-gated channels (Khorkova and Golowasch, 2007;Schulz et al, 2007;Temporal et al, 2012;Tran et al, 2019), but it is not known to which degree synaptic currents may be co-regulated. Variability of synaptic currents could be compensated for by variability in intrinsic currents, as has been suggested for the leech heartbeat system (Gunay et al, 2019), and as is implicit in theoretical work that shows similar circuit activity with different combinations of intrinsic and synaptic current levels (Prinz et al, 2004b;Onasch and Gjorgjieva, 2020). Alternatively, compensatory co-regulation of intrinsic currents could lead to consistent neuronal excitability on its own, and variability of synaptic trajectory then must be constrained to allow for consistent phases.…”
Section: Variability and Co-regulationmentioning
confidence: 97%
See 1 more Smart Citation
“…Variability of intrinsic currents in STG neurons may be compensated by cell-type-specific co-regulation of different voltage-gated channels (Khorkova and Golowasch, 2007;Schulz et al, 2007;Temporal et al, 2012;Tran et al, 2019), but it is not known to which degree synaptic currents may be co-regulated. Variability of synaptic currents could be compensated for by variability in intrinsic currents, as has been suggested for the leech heartbeat system (Gunay et al, 2019), and as is implicit in theoretical work that shows similar circuit activity with different combinations of intrinsic and synaptic current levels (Prinz et al, 2004b;Onasch and Gjorgjieva, 2020). Alternatively, compensatory co-regulation of intrinsic currents could lead to consistent neuronal excitability on its own, and variability of synaptic trajectory then must be constrained to allow for consistent phases.…”
Section: Variability and Co-regulationmentioning
confidence: 97%
“…Synaptic currents also vary substantially across individuals and their magnitude is correlated with relative timing of the burst onset of the postsynaptic neuron ( Goaillard et al, 2009 ). In theoretical work, the magnitude of synaptic currents has been varied and tuned alongside voltage-gated conductances to show which combinations and possible mechanisms give rise to similar activity ( Prinz et al, 2004b ; O’Leary et al, 2014 ), and it has been suggested that the relative synaptic strengths must be different in individual animals to produce observed activity phases ( Günay et al, 2019 ). However, it is unknown whether synaptic currents co-vary with individual voltage-gated currents in a correlated manner to compensate for variability in intrinsic neuronal excitability.…”
Section: Introductionmentioning
confidence: 99%
“…Variability of intrinsic currents in STG neurons may be compensated by cell-type-specific co-regulation of different voltage-gated channels (Khorkova and Golowasch, 2007;Schulz et al, 2007;Temporal et al, 2012;Tran et al, 2019), but it is not known to which degree synaptic currents may be co-regulated. Variability of synaptic currents could be compensated for by variability in intrinsic currents, as has been suggested for the leech heartbeat system (Gunay et al, 2019), and as is implicit in theoretical work that shows similar circuit activity with different combinations of intrinsic and synaptic current levels (Prinz et al, 2004a;Onasch and Gjorgjieva, 2020). Alternatively, compensatory co-regulation of intrinsic currents could lead to consistent neuronal excitability on its own, and variability of synaptic trajectory then must be constrained to allow for consistent phases.…”
Section: Variability and Co-regulationmentioning
confidence: 97%
“…It is now well-established that multiple sets of maximal conductances of ion channels can produce very similar neuronal activity patterns in both individual neurons and circuits ( 1 10 ). Nonetheless, it is also clear that models of desired intrinsic properties are relatively rarely found by randomly sampling within a space of parameters ( 5 , 6 , 11 ). Thus, it is likely that biological neurons use homeostatic and other developmental mechanisms to successfully find rare sets of values of ion channel conductances that give rise to specific patterns of intrinsic excitability ( 12 16 ).…”
mentioning
confidence: 99%